(untitled) (City: History, Culture, Society, 2019)
This article deals with the concept of the periphery and its definition in the early 18th century. According to Peter Burke and his reflections in «History and Social theory», the known dichotomy «centre-periphery» (I. Wallerstein) can be employed in historical studies, not only in political or economic research. Therefore we aim to analyze the travel diary written by the Danish ambassador Just Juel within his diplomatic mission to Muscovy (1709–1711) and outline his main impressions and conclusions on the early-modern Russian cities and other «issues» (e.g. road infrastructure, economy, communication systems, architecture, food market) which later contribute to the image of Russia in the early modern epoch. This ego-narrative contains some prevailing views of Russia as the European periphery: distant, uncivilized, poorly connected with the rest of the continent, economically and politically underdeveloped country. Also, this travel account shapes peculiar Danish perception of the early-modern Petrine Russia and its location on the mental map.